(untitled) (Research, Society and Development, 2021)
Acetylsalicylic acid or aspirin is the most widely used drug globally for its anti-inflammatory characteristics, although little is known about its actions on the central nervous system (CNS). We investigated aspirin’s potential neuroprotective effects against paraquat-induced neurotoxicity (PQ) in the present study. Adult male wild-type flies were exposed to a diet containing PQ (3 mM) and/or aspirin (1 μM; 5 μM; 10 μM). Flies fed with PQ reduced locomotion and increased mortality. PQ-induced neurotoxicity has also been associated with a marked decrease in acetylcholinesterase (AChE) activity and lipid peroxidation. Co-exposure to aspirin (5 μM) increased survival, improved motor performance, increased AChE activity, and decreased lipid peroxidation. Our results suggest aspirin’s neuroprotective effects, probably due to its lysosomal action and antioxidant characteristics. Thus, we demonstrate that the Drosophila melanogaster model can elucidate basic aspirin mechanisms to assist the evaluations carried out in higher animals to minimize the neurodegenerative effects caused by diseases such as Parkinson’s and Alzheimer’s.